2001
DOI: 10.1002/pc.10517
|View full text |Cite
|
Sign up to set email alerts
|

Conducting aluminum‐filled nylon 6 composites

Abstract: This work is concerned with the preparation and characterization of composite materials prepared by compression molding of a mixture of aluminum flakes and nylon 6 powder. The electrical conductivity, density, hardness and morphology of composites were investigated. The electrical conductivity of the composites is < lo-' S/cm unless the metal content reached the percolation threshold, beyond which the conductivity increased markedly by as much as loll. The volume fraction of conductive filler at the percolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…The procedure used to estimate the conductivity from resistance in this study was similar to one reported earlier. 21 The density of the composites was measured in accordance with ASTM D 792-91 by the difference of weight in the air or with the sample immersed in water, as the liquid of known density, at 23°C with a Mettler Toledo (Columbus, OH) AJ 100 balance equipped with a density-determination kit.…”
Section: Composite Characterization Techniquesmentioning
confidence: 99%
“…The procedure used to estimate the conductivity from resistance in this study was similar to one reported earlier. 21 The density of the composites was measured in accordance with ASTM D 792-91 by the difference of weight in the air or with the sample immersed in water, as the liquid of known density, at 23°C with a Mettler Toledo (Columbus, OH) AJ 100 balance equipped with a density-determination kit.…”
Section: Composite Characterization Techniquesmentioning
confidence: 99%
“…At first, carbon black [1,2], metallic powder [3][4][5], polyaniline [6] and graphite [7] were used as electrical reinforcement in polymer, but high concentration was necessary to achieve the percolation threshold which endangered the mechanical properties of the nanocomposites due to the formation of agglomerations. Later, several researchers proposed polymer nanocomposites reinforced with graphene nanoparticles and its derivatives (expanded graphite, graphene nanoplatelets, graphite oxide, functionalized graphene/expanded graphite), which are able to form more stable 3D conductive networks in lower volume content as a consequence of their high aspect ratio (AR-ratio of main particle dimension to minor one) [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the percolation threshold of PES/untreated and PES/treated graphite composites is lower than 3 wt% which is much lower than that of composites prepared with conventional (micro-scale) graphite [10]. The improvement in conductivity of the composites at low loading could be attributed to high aspect ratio of the graphite.…”
Section: Effect Of Addition Of Graphite On Electrical Conductivity Ofmentioning
confidence: 61%
“…In most cases, relatively large quantities of fillers are needed to reach the critical percolation value, as the filler particle size is at micrometer scales. Too high concentration of the conductive filler could lead to materials redundancy and detrimental mechanical properties [10]. The electrical conductivity of composites, filled with micron sized carbon fibres, with the lowest aspect ratio (10) loaded as high as 60 wt% was the similar as compared to 10wt% of the one with highest aspect ratio (300) [2][3][4][5][6].…”
mentioning
confidence: 99%